2021
DOI: 10.1186/s12891-021-04393-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-elective and revision arthroplasty are independently associated with hip and knee prosthetic joint infection caused by Acinetobacter baumannii: a Brazilian single center observational cohort study of 98 patients

Abstract: Background Prosthetic joint infection (PJI) caused by Acinetobacter baumannii (Ab) has become a growing concern due to its overwhelming ability to express resistance to antibiotics and produce biofilm. Aim This study aimed to identify independent risk factors (RFs) associated with Ab-associated PJI and their role in the treatment outcome. Methods This was a single-centre, retrospective cohort study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The reason for the high frequency of periprosthetic joint infection (PJI) in single/multi-center studies might be that TKA revisions related to PJI are generally considered extremely complicated and expensive [ 22 , 23 ]. Meanwhile, revisions related to aseptic loosening and other mechanical drawbacks might be considered “simple” revisions and tend to be performed in local hospitals, whereas PJI-related revisions are more frequently referred to specialized orthopedic centers with experience and sufficient resources [ 20 , 24 ]. This also explains why the proportion of patients with PJI in the present study was higher than that reported in some other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the high frequency of periprosthetic joint infection (PJI) in single/multi-center studies might be that TKA revisions related to PJI are generally considered extremely complicated and expensive [ 22 , 23 ]. Meanwhile, revisions related to aseptic loosening and other mechanical drawbacks might be considered “simple” revisions and tend to be performed in local hospitals, whereas PJI-related revisions are more frequently referred to specialized orthopedic centers with experience and sufficient resources [ 20 , 24 ]. This also explains why the proportion of patients with PJI in the present study was higher than that reported in some other studies.…”
Section: Discussionmentioning
confidence: 99%
“…174,267,268 Infections caused by A. baumannii represent ~2% of all healthcare-associated infections in the U.S. and Europe, 269 and globally, ~45% of all A. baumannii isolates are multidrug resistant, further complicating clinical outcomes. 270,271 The rate of orthopedic implant-associated A. baumannii infections range from 0.6%-28.7%, [272][273][274] with a mortality rate of 30.7%, 274,275 and these infections are an increasingly common cause of osteomyelitis and delayed healing in soldiers with orthopedic battlefield wounds. [276][277][278] Furthermore, recent study by Choe et al 268 showed that A. baumannii inhibited implant osseointegration when investigated in a murine model of infection.…”
Section: Gram-negative Organisms In Pji and The Effect Of D-aasmentioning
confidence: 99%